Causes and Consequences of Deviant Behaviour among Polytechnic Students in Oyo State, Nigeria - FAD I PE, Rasaq Abimbola; AJOKPANIOVO, Michael; K AYODE, Olajide Charles; UWADIA, John Chukwuewene (International Journal of Educational Management, 2025)
This study investigated causes and consequences of deviant behaviour among polytechnic students in Oyo State. Descriptive survey design was adopted. The population is all polytechnic students in Oyo State, while the target population are selected students of Oke-Ogun polytechnic, Federal School of Surveying, and Polytechnic of Ibadan. Simple random sampling technique was used to select four hundred and nineteen respondents but four hundred and five were retrieved and analyzed. The instrument, titled: "Causes and Consequences of Deviant Behaviour Questionnaire" was used to elicit information from the respondents. Both descriptive and inferential statistics were used for the data analysis. The findings revealed that deviant behaviour is caused by poor parental relationship, negative mass media, and negative peer group influence. The study revealed that deviant behaviour leads to school dropout, poor academic performance andabuse of substances among polytechnic students. No significant differences were found on the causes of deviant behaviour among polytechnic students based on age and religion, and no significant difference were found on the consequences of deviant behaviour among polytechnic students based on age and religion. It was recommended that counsellors should regularly sensitize students with the right information on the causes and negative consequences of deviant behaviours. School administrators, lecturers and counsellors should work together in curbing deviant behaviour exhibited by students in schools.